2016
DOI: 10.1111/odi.12428
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of oral diseases: emerging concepts, management and interplay with systemic health

Abstract: Oral disease remains a major public health burden worldwide. It is of great importance to integrate oral health into global health agenda via the common risk factor approach. The long-term sustainable strategy for global oral health should focus on health promotion and disease prevention through effective multidisciplinary teamwork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
478
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(499 citation statements)
references
References 77 publications
1
478
0
20
Order By: Relevance
“…Periodontal diseases and tooth decay may be exacerbated without good oral hygiene. Oral health is also significantly associated with various systemic diseases such as cardiovascular disease, diabetes mellitus, chronic respiratory disease and rheumatoid arthritis (1)(2). Previous studies have examined the impact of socioeconomic status (SES) on the health-related behaviors of adults (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal diseases and tooth decay may be exacerbated without good oral hygiene. Oral health is also significantly associated with various systemic diseases such as cardiovascular disease, diabetes mellitus, chronic respiratory disease and rheumatoid arthritis (1)(2). Previous studies have examined the impact of socioeconomic status (SES) on the health-related behaviors of adults (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Untreated caries in permanent teeth was the most prevalent condition evaluated for the entire GBD [Global Burden of Disease] 2010 Study with a global prevalence of 35% for all ages combined [2]. WHO report found that oral cancer and caries increased markedly by an average of 45.6% from 1990 to 2010 in parallel with the major non-communicable diseases like diabetes by 69.0% [3]. Pediatric Oral and maxillofacial surgery is an area of special interest within dentistry as the presentation and management of oral and maxillofacial disorder's in children differ from adults in nature and severity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…4 Several medical disorders are associated with ulcers. 5 This might suggest that RAS has pathways in common with other diseases. Despite its high prevalence, the etiology and pathogenesis of RAS still remains unclear.…”
Section: Introductionmentioning
confidence: 99%